Morphology, chemical reaction mechanism, and cross-linking degree of asphalt binder modified by SBS block co-polymer. (16th May 2023) - Dong, Fuqiang; Yang, Peixing; Yu, Xin; Jiang, Mengmeng; Wang, Shiyu; Zu, Yuanzhe; Chen, Bei; Wang, Jincheng
Graphical abstract: Highlights: The reaction conditions have great influence on the performance of SBS modified asphalt. The stabilizer content is the key factor for the performance improvement of SBS modified asphalt. The PB segment in the SBS polymer participates in the chemical reaction. The cross-linking percentage of SBS modified asphalt is about 13%. Abstract: Recently, the batch production of styrene–butadienestyrene (SBS) modified asphalt has been realized, but quality control is still in the empirical stage. While the chemical reaction position and the cross-linking degree are unclear, affecting the controlling quality of SBS modified asphalt. Therefore, this study investigated the influence of the reaction conditions and the stabilizer content on the performance and morphology of the SBS modified asphalt. And whether the chemical reaction exists and the chemical reaction position were confirmed by preparing the polystyrene (PS) monomer, polybutadiene(PB) monomer, and SBS modified asphalt with and without stabilizer. Finally, the fluorescence microscope (FM) test, Fourier transformation infrared spectroscopy (FTIR) test and the chemical titration method were used to characterize quantitatively the microstructure changes of SBS modified asphalt. The results show that the reaction conditions greatly influence the performance of SBS modified asphalt. After adding the stabilizer, the phase state of the system changed from the SBS phase as a dispersed phase and the asphalt phase as a continuous phase to the double continuous phase, and the network structure was formed. The chemical reaction has taken place in the PB and SBS modified asphalt, and the PB segment of the SBS polymer participates in the chemical reaction. Furthermore, the degree of cross-linking reaction of SBS modified asphalt is low, and the range of the cross-linking percentage is about 12.3%-14.5%.